2013
DOI: 10.1007/s13300-013-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Switching from Insulin Glargine or Detemir to Insulin Degludec in Patients with Type 1 Diabetes Mellitus

Abstract: IntroductionInsulin degludec is a new, ultra-long-acting basal insulin. The aim of this study was to analyze the changes of basal insulin dose and blood glucose profile in basal–bolus therapy of type 1 diabetes mellitus (T1DM) at the switching of basal insulin from insulin glargine or detemir to insulin degludec.MethodsSixteen patients with T1DM were enrolled. The patients underwent continuous glucose monitoring before and after the switching of insulin glargine or detemir to degludec. Ten patients treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
(29 reference statements)
5
22
0
Order By: Relevance
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The 2-year extension of the main BEGIN trial [22] indicated that the hypoglycemia-reducing benefits of IDeg were observed at night, rather than during the day; this is likely because a relationship exists between bolus insulin and diurnal hypoglycemia, whereas the ultra-long acting and less variable glucose-lowering effects of IDeg may better decrease nocturnal hypoglycemia. Some other studies [9,13,[17][18][19][23][24][25][26], including our recent study [14], also demonstrated a greater reduction in the risk of nocturnal hypoglycemia, rather than an overall decrease, with IDeg in all-aged patients with type 1 diabetes. The outcomes of an earlier 1-year study of IDeg in Japanese adults with type 2 diabetes were consistent with our observations [11].…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, the daily dose of IDeg was numerically decreased, but did not significantly differ during the 24-week study period relative to the baseline; therefore, the administration of a conservative dose is recommended in children of age<15 years with type 1 diabetes upon switching from IGlar previously given once daily to IDeg. Subsequently, this dose can be adjusted according to the patient's blood glucose levels to avoid occurrence of hypoglycemia [9,11,18,19,[24][25][26]. The dose-adjustment could affect a risk of hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In recent Japanese reports, Kusunoki et al [27] demonstrated that PG levels during evening time tended to decrease after switching to IDeg from other Las as evaluated by CGM in patients with once-daily injection of La at baseline. Nakamura et al [28] showed that the mean and SD of FPG were significantly smaller at lower dose of insulin with IDeg than with IGlar in a multicenter, randomised, crossover study for adults with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the same group has published two reports assessing the effects of Deg and Gla using CGM with a test diet [9,10]. Patients with type 1 diabetes were switched from Gla or detemir to Deg and followed for 12 or 24 weeks.…”
Section: Insulin Dose (Table 2)mentioning
confidence: 99%
“…Although the phase 3 trials of Deg showed good performance as a new basal insulin in people with type 1 diabetes [6][7][8], few studies have shown the effect of Deg on the stability of glucose levels using continuous glucose monitoring (CGM) [9,10]. CGM systems allow visualization of the daily variations in blood glucose levels, facilitating the detection of postprandial hyperglycemia and asymptomatic hypoglycemia.…”
mentioning
confidence: 99%